Multistate Comparison of Attractants and the Impact of Fruit Development Stage on Trapping Drosophila suzukii (Diptera: Drosophilidae) in Raspberry and Blueberry. Issue 4 (14th April 2018) - Jaffe, Benjamin D; Avanesyan, Alina; Bal, Harit K; Feng, Yan; Grant, Joshua; Grieshop, Matthew J; Lee, Jana C; Liburd, Oscar E; Rhodes, Elena; Rodriguez-Saona, Cesar; Sial, Ashfaq A; Zhang, Aijun; et al.
Abstract: Spotted-wing drosophila, Drosophila suzukii Matsumura (Diptera: Drosophilidae), is an invasive pest of soft-skinned fruits across the globe. Effective monitoring is necessary to manage this pest, but suitable attractants are still being identified. In this study, we combined lures with fermenting liquid baits to improve D. suzukii trapping specificity and attractiveness. We also measured the efficiency and specificity of baits/lures during different times of the season; the reproductive status of females among baits/lures; and the effects of locations and crop type on these response variables. We developed a metric that combined mating status and fat content to determine differences in types of females attracted. Lures utilizing yeast and sugar-based volatiles trapped the most D. suzukii . The addition of a commercial lure to yeast and sugar-based lures increased catches in most locations, but was also the least specific to D. suzukii . Apple juice-based chemical lures tended to be most specific to D. suzukii, while lures comprised of a singular attractant tended to trap more D. suzukii with a higher reproductive potential than combinations of attractants. Trap catch and lure specificity was lower during fruit development than fruit ripening. While catch amounts varied by geographic location and crop type, attractants performed similarly relative to each other in each location and crop. Based on the metrics in this study, the yeast and sugar-based attractants were the most effective lures. However, further work is needed to improve early season monitoring, elucidate the effects of physiological status on bait attraction, and understand how abiotic factors influence bait attraction.